Tropical mountains as natural laboratories to study global changes: A long-term ecological research project in a megadiverse biodiversity hotspot - Silveira, Fernando A.O.; Barbosa, Milton; Beiroz, Wallace; Callisto, Marcos; Macedo, Diego R.; Morellato, Leonor Patrícia Cerdeira [UNESP]; Neves, Frederico S.; Nunes, Yule R.F.; Solar, Ricardo R.; Fernandes, G. Wilson (Elsevier, 2019)
Campo rupestre is a megadiverse vegetation mosaic dominating one of the world's geologically oldest tropical mountains. The campo rupestre hosts nearly 15% of Brazil's flora, with 40% of endemism in an area smaller than 1% of the national territory. Here, we summarize and explain the rationale underlying the long-term ecological research at Serra do Cipó (LTER-CRSC), in southeastern Brazil. The LTER-CRSC is a multi-taxa monitoring initiative focused on ecological patterns and processes along elevational gradients. We explain the standardized sampling methods of the LTER-CRSC and provide original data on climate, soil, and biodiversity along an elevational gradient. In our view, the LTER-CRSC offers a remarkable opportunity to improve predictions on how global change drivers affect biodiversity and ecosystem functioning in tropical, snow-free mountains. Our ultimate goal is to integrate the data from this study into a growing database from global mountain assessment networks and LTERs. We hope this initiative will stimulate collaboration and lead to further LTER sites being established in tropical mountains. Such efforts are needed as a basis for scientifically-based policy making, especially aimed at mitigating the effects of global change on tropical biodiversity and ecosystem functioning.
Keywords: Cerrado; Elevation; Espinhaço range; Long-term ecological research; Monitoring; Rupestrian grassland